2017
DOI: 10.1063/1.4989465
|View full text |Cite
|
Sign up to set email alerts
|

Planarizing cytosine: The S1 state structure, vibrations, and nonradiative dynamics of jet-cooled 5,6-trimethylenecytosine

Abstract: We measure the S → S spectrum and time-resolved S state nonradiative dynamics of the "clamped" cytosine derivative 5,6-trimethylenecytosine (TMCyt) in a supersonic jet, using two-color resonant two-photon ionization (R2PI), UV/UV holeburning, and ns time-resolved pump/delayed ionization. The experiments are complemented with spin-component scaled second-order approximate coupled cluster (SCS-CC2), time-dependent density functional theory, and multi-state second-order perturbation-theory (MS-CASPT2) ab initio c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…It appears that the amino group at C2 tends to provide an efficient access to a conical intersection while oxygen substitution at C2 tends to have the opposite effect. This observation is consistent with computations by Szabla et al 104 By contrast, the isoG dynamics does resemble that of C with the C5-C6 bond immobilized, similar to the "planarized" cytosine structure of trimethylenecytosine, reported by Traschel et al 43 The reported pump−probe results for enol C were not obtained at the 0−0 transition but rather on the rising edge of its broad initial absorption region. (**) For Isoguanine we cannot be sure whether we observe KA1, KA2, or a mixture of both.…”
Section: Tautomerssupporting
confidence: 90%
See 1 more Smart Citation
“…It appears that the amino group at C2 tends to provide an efficient access to a conical intersection while oxygen substitution at C2 tends to have the opposite effect. This observation is consistent with computations by Szabla et al 104 By contrast, the isoG dynamics does resemble that of C with the C5-C6 bond immobilized, similar to the "planarized" cytosine structure of trimethylenecytosine, reported by Traschel et al 43 The reported pump−probe results for enol C were not obtained at the 0−0 transition but rather on the rising edge of its broad initial absorption region. (**) For Isoguanine we cannot be sure whether we observe KA1, KA2, or a mixture of both.…”
Section: Tautomerssupporting
confidence: 90%
“…Leutwyler and coworkers have demonstrated similar trends for cytosine (C), where immobilizing the C5=C6 bond by a five membered ring leads to orders of magnitude longer excited state lifetime. 43 The bottom row compares a series of purines in which those with an unsubstituted C2adenine and hypoxanthinehave ultrashort lifetimes. Those with a substituent at C2 have much longer excited state lifetimes.…”
Section: Derivativesmentioning
confidence: 99%
“…49 Similar excited-state dynamics and lifetimes of B1 ns were also reported for jet-cooled 5,6-trimethylenecytosine, which resembles isoG structurally. 74,75 The 5,6-trimethylenesubstituent was suggested to lock the planarity of the aromatic pyrimidine ring and hinder ring-puckering motions 74,75 which enable the formation of pp*/S 0 state crossings in canonical C. 45 Most importantly, the resulting low photostability of keto isoG is consistent with the prebiotic scenario assuming that intense UV irradiation was one of the crucial selection factors for RNA constituents on an early Earth. This observation, together with the population of multiple tautomeric forms in bulk water and potential wobble base pairing make isoG a much less reliable component of primordial informational polymers than its biological counterpart.…”
Section: Discussionsupporting
confidence: 67%
“…[3][4][5][6] Among all nucleobases, cytosine (Cy) and its derivatives are probably the most studied system experimentally in the gas phase. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Ultrafast excited-state dynamics of Cy in the gas phase has been explored by several groups. [22][23][24][25][26] Our group has previously used femtosecond pump-probe photoionization spectroscopy to investigate the ultrafast excited-state dynamics of Cy and its microsolvated complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[33][34][35][36][37][38][39][40][41] The importance of this C5-C6-twisting ethylenic type CI has been supported by the observation of a dramatic lengthening of the 1 ππ* state lifetime in 5,6-trimethylenecytosine in which the C5-C6 bond of Cy ring is covalently clamped with a trimethylene bridge. [14,16,45] Thus, it is intriguing to explore how methylation at the C5 position influences the energetics of this CI and the associated relaxation dynamics. Ultrafast measurements of 5mCy and its derivatives in aqueous solutions have been reported, [46,47] but direct femtosecond pump-probe measurements in the gas phase are still lacking.…”
Section: Introductionmentioning
confidence: 99%